The Voice of Holland: Allograph Production in Written Dutch Past Tense Inflection. Issue 3 (3rd July 2017) - de Bree, Elise; van der Ven, Sanne; van der Maas, Han
ABSTRACT: According to the Integration of Multiple Patterns hypothesis (IMP; Treiman & Kessler, 2014), the spelling difficulty of a word is affected by the number of cues converging on the correct answer. We tested this hypothesis in children's regular past tense formation in Dutch. Past tenses are formed by adding either- de or- te to a verb stem. Despite instruction, children often choose the wrong allograph. In a large dataset (227 items, together completed 392, 802 times) from an online language program we assessed whether morphophonological and orthographic cues determine differences in difficulty and explain error patterns. Regression analyses established that inflection difficulty was affected by number of converging cues, especially morphophonological and orthographic cues. Error analyses further showed that allograph errors were prominent when graphotactic frequency and especially voicing probability collided with the correct answer. The results match and specify the IMP. Proposals are made to use this knowledge in educational practice.